Distribution of dinoflagellate cyst assemblages in surface sediments of Magellan fjords and channels (Patagonia, Chile) with a focus on harmful species: An overview on environmental scenario. (April 2023) - Salgado, Pablo; Pizarro, Gemita; Frangopulos, Máximo; Pinto-Torres, Marco; Toro, Carolina; Torres, Rodrigo; Alarcón, Emilio; Guzmán, Leonardo; Manríquez, Karen; Raimapo, Roberto; Cascales, Emma
Highlights: High diversity of dinoflagellate cysts. P. dalei and P. conicoides the most abundant and frequent species. Toxin producers A. catenella, A. ostenfeldii and P. reticulatum were recorded. P. reticulatum and G. spinifera cysts were very abundant in Inutil Bay. Abstract: Several dinoflagellate species form benthic resting cysts in their life cycle. In order to study the composition, abundance and distribution of cyst assemblages, with a focus on harmful species, thirty-one surface sediment samples from the Magellan fjords and channels system were analysed. In situ (temperature, salinity, inorganic nutrients, dissolved oxygen, organic matter, and chlorophyll- a ) and five-year (salinity, temperature, dissolved oxygen, and chlorophyll- a ) measurement data were analysed to obtain an overview on environmental scenario. A total of 56 cyst morphotypes were recorded, some of which were identified for the first time for the Chilean coast ( Dactylodinium cf. arachnoides, Impagidinium cf. velorum, Archaeperidinium sp., Protoperidinium haizhouense, Protoperidinium sinuosum, Protoperidinium tricingulatum, and Dubridinium cf. ulsterum ). In vitro germination of cysts allowed the vegetative form of the species of the order Suessiales to be determined. Total cyst concentrations were highly variable, ranging from 145 to 5453 cysts mL −1 of wet sediment (mean 1246 ± 1061 cysts mL −1 ), with the lowest cyst values in the area adjacent to the Southern Patagonian Ice Field. Pentapharsodinium dalei and Protoperidinium conicoides generally dominated (%) the cyst assemblages. The harmful species Alexandrium catenella and Alexandrium ostenfeldii were not abundant and sparsely distributed, while Protoceratium reticulatum was widespread and highly abundant with Gonyaulax spinifera in Inutil Bay (Magellan Strait). Cluster and nMDS analyses performed with cyst concentrations of the 56 taxa in the 31 stations formed seven cyst assemblage clusters, reflecting high environmental variability. Canonical correspondence analyses performed with cyst concentrations and in situ and long-term environmental data showed different ecological signals, demonstrating that in situ parameters must be used carefully when studying cysts in surface sediments.